2017
DOI: 10.4236/jmmce.2017.52007
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear Behavior of Aluminum 6063 Composites Reinforced with TiB<sub>2</sub> Particles

Abstract: The influence of titanium diboride (TiB 2 ) loading on the dry sliding wear characteristics of aluminum 6063 matrix alloy-titanium diboride (Al/TiB 2 ) composite materials has been assessed using a pin-on disc wear tester at different loads. The composites with 5 and 10 wt% of fine TiB 2 particles were fabricated using stir casting technique. For comparison, as-cast of the base alloy were made under the same processing applied for Al/TiB 2 composites. The hardness of the composite materials was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
2
Order By: Relevance
“…Increment in density values depicts that the breakage of particles may not have any noticeable impact on the fabricated composites. 38 This can further be attributed to uniform dispersion of TiB 2 particles and improvement in matrixreinforcement bonding. It can be concluded that the stir casting technique is ideal for efficient manufacturing of composites.…”
Section: Sem Analysismentioning
confidence: 97%
“…Increment in density values depicts that the breakage of particles may not have any noticeable impact on the fabricated composites. 38 This can further be attributed to uniform dispersion of TiB 2 particles and improvement in matrixreinforcement bonding. It can be concluded that the stir casting technique is ideal for efficient manufacturing of composites.…”
Section: Sem Analysismentioning
confidence: 97%
“…The same trend was noted for all sliding speeds. [25,27,28]. due to complex processes that occurred during wear of the composites.…”
Section: Effect Of Reinforcement On Hardnessmentioning
confidence: 99%
“…Bunun muhtemel nedeni matris içerindeki TiB2 partikülleri sertlik artışına neden olarak aşındırıcı partiküllerinin aşınan yüzeylere penatrasyonunu azaltarak aşınma kayıplarının azalmasına neden olmuştur. TiB2 takviyeli alüminyum matrisli kompozitlerin aşınma davranışı üzerine yapılan bir çok çalışmada TiB2 partiküllerinin ilavesi ile kompoztlerin sertlik değerlerini artırmasına bağlı olarak kompozitlerin aşınma özelliklerinin iyileştiği rapor edilmiştir (Kumar et al, 2007) (Kumar, Chakraborty, Subramanya Sarma, & Murty, 2008) (Kumar, Subramanya Sarma, & Murty, 2009) (Krishnamurthy et al, 2017). Şekil 7'de verilen aşınma izlerine ait optik görüntüler TiB2 ile güçlendirilmiş bölgelerde aşınma kayıplarının daha düşük olmasının nedenini açıklamaktadır.…”
Section: şEkil 5 Tib2/al Ve Tib2/al-cu Kompozitlerin Ve çElik Malzemunclassified
“…K. L. Tee (Tee et al, 2010) arkadaşları alüminyum matrise % 15 TiB2 ilavesi ile çekme gerilmesinin %56,5, akma gerilmesinin %65,7 ve elastik modülün % 21,5 oranında artırdığını rapor etmişlerdir. K. Krishnamurthy (Krishnamurthy, Ashebre, Venkatesh, & Suresha, 2017) ve arkadaşları ise 6063 alüminyum alaşımına TiB2 ilavesi ile spesifik aşınma hızının azaldığını göstermişlerdir. Kumar (Kumar, Sarma, & Murty, 2007) ve arkadaşları Al-5Cu matrise TiB2 ilavesi ile abrasif aşınma direncinin iyileştiğini belirtmişlerdir.…”
Section: Introductionunclassified